On the (Un)greenness of Biocatalysis: Some Challenging Figures and Some Promising Options - Domínguez de María, Pablo; Hollmann, Frank (Frontiers in Microbiology, 2015)
Biocatalysis is generally regarded as a ‘green’ technology. This statement is justified by the mild reaction conditions, the use of aqueous reaction media – with water as the paradigm of green solvents –, and the renewable nature of the biocatalysts. However, researchers making these statements frequently do not take into account the entire picture of their processes. Aspects like water consumption, wastewater production, titers and metrics of the (diluted?) biocatalytic processes are important as well. With those figures at hand, many biocatalytic reactions do not appear so green anymore. This article critically discusses some common wrong assumptions given for biocatalytic approaches, with regard to their environmental impact and actual greenness. Some promising biocatalytic approaches, such as the use of biphasic systems involving biogenic solvents, deep-eutectic-solvents (and biogenic ionic liquids), water-free media, solvent-free processes, are briefly introduced, showing that enzyme catalysis can actually be a robust sustainable alternative for chemical processes.